Fasting and glucose induced thermogenesis in response to three ambient temperatures: a randomized crossover trial in the metabolic syndrome. Issue 10 (October 2018) - Pathak, K.; Woodman, R.; James, A.; Soares, M.
Abstract Background/objectives Cold exposure increases thermogenesis and could improve insulin sensitivity. We hypothesized a blunted response in the metabolic syndrome (MetS). Subjects/methods Twenty older adults 59 ± 10.4 years (with MetS, MetS+, n  = 9; without MetS, MetS−, n  = 11) completed a randomized crossover design of 3.5 h exposures to 20, 25 and 27 °C on three visits. After an hour's rest at the desired temperature, resting metabolic rate (RMR), respiratory quotient (RQ), forearm to fingertip gradients (FFG), and in the ear temperature (IET) were measured over 30 min. An oral glucose tolerance test followed, and serial measurements were continued for 2 h. Venous blood was sampled for clinical chemistry, irisin, and fibroblast growth factor 21(FGF21). A mixed model ANCOVA adjusted data for age, gender, fat mass, fat-free mass and seasonality. Results There was a significant MetS×temperature interaction where adjusted RMR was significantly higher in MetS+ compared to MetS− by 12% at 20 °C and by 6% at 25 °C, but similar at 27 °C. FFG increased and IET decreased with decreasing temperature to the same extent in both groups. Fasting irisin and FGF21 did not vary with temperature but the former was significantly higher in MetS−. Adjusted postprandial RQ and insulin to glucose ratios were significantly higher at 20 °C relative to 25 °C. Partial correlation analysis of differences between 27 and 20 °C indicated significant positive relationships between fasting as well as postprandial RQ and the respective changes in irisin and FGF21. Conclusions There could be an upward shift of the TNZ in MetS+, but this needs reevaluation.